Drugs misuse among children: measuring the level of parents’ awareness on their children’s behavioural change / Afifah Hanani Rosdi, Abdul Rauf Ridzuan and Siti Hajar Abdul Aziz - Rosdi, Afifah Hanani; Ridzuan, Abdul Rauf; Abdul Aziz, Siti Hajar (Faculty of Communication & Media Studies, 2019)
A survey was carried out to gather information on awareness of parents on children in relation to drug misuse matters. Significantly, parents are aware of the factors affecting their children’s behaviour, which was causes by the influence of parents’ knowledge on the drugs-related issues, circle of friends, social pressure, and parental behaviour. This study referred to Social Bonding Theory as its reference to compare the results of the findings with the existing theory. Meanwhile, based on Raosoft Calculator software, since the population size of the study is 8.15 million, hence 90% level of confidence was used to describe the amount of uncertainty the researcher can tolerate. The response distribution is 70% whereby it is the probability distribution of the response (target) variable. Thus, as calculated in the software, the recommended sample size is 228 respondents. In this study, the researcher managed to gather 242 respondents through purposive sampling method in order to identify the level of awareness of parents on their children’s behavioural change. The R2 obtained = 0.401 defines that 40.1% of the amount of variance in the awareness of parents on their children’s behavioural change can be explained by the independent variables.